Михайло Юлiанович Брайчевський як Моральний авторитет української iсторичної науки та археологiї - Залізняк, Л.Л. (Археологія, 2019)
Робиться спроба аналізу деяких поглядів видатного українського археолога та історика М. Ю. Брайчевського на складні проблеми слов’яногенезу та україногенезу. В статье анализируются взгляды выдающегося украинского археолога и историка М. Ю. Брайчевского на сложные проблемы славяногенезиса и украиногенезиса. В изучении проблемы происхождения славян и украинского народа ученый опирался на собственную стройную, продуманную этно-генетическую модель. Она отвечает строгим требованиям современной этнологии. Исследователь работал над ней до конца своей жизни. М. Ю. Брайчевского был сторонником понимания археологических культур как следов древних этносов, а язык и культура являлись непосредственным отраженим этноса. По мнению ученого, проблема этногенезиса междисциплинарна. Она опирается на данные истории, археологии, языкознания, этнографии, антропологии. М. Ю. Брайчевский был сторонником происхождения украинцев от племен антов раннего средневековья. Он отрицал существование в прошлом единого древнерусского языка, в результате разделения которого якобы появились отдельные восточно-славянские народы. По мнению М. Ю. Брайчевского, ключевой проблемой истории Восточной Европы есть историческое наследие Киевской Руси. С позиций современной европейской этнологии население Южной Руси Х—ХIII вв. во главе с княжескими Киевом, Переяславлем, Галичем имели древнеукраинскую этно-языковую специфику, то есть фактически было украинцами на средневековом этапе развития. Киевская Русь никак не могла быть первым этапом российской государственности, так как возникла она задолго до рождения самих россиян, считал ученый. Киевская Русь была продуктом государственного строительства древнеукраинцев на средневековом этапу их развития. Аналитическое мышление, энциклопедическая эрудированность, патриотическая принципиальность возвышали Михаила Юлиановича над украинскими историками и археологами 1960—1980-х гг. The views of the prominent Ukrainian archaeologist and historian of M. Yu. Braichevskyi on the complicated problems of the Slavs genesis and Ukrainian genesis are analyzed in the article. In the study of problem on the Slavs and Ukrainian people origin the scientist based on the own well-composed, carefully considered ethnogenesis model. It answers the strict requirements of modern ethnology. A researcher worked on it to the end of his life. He was the supporter of understanding archaeological cultures as tracks of ancient ethnos, and a language and culture are by itself the direct reflection of the ethnos. In the scientist’s opinion the problem of ethnogenesis is interdisciplinary. It is based on the history, archaeology, linguistics, ethnography, anthropology data. M. Yu. Braichevskyi was the follower of the Ukrainians origin from the Antes of early Middle Ages. He denied the existence of the common Old Rus language in the past, as a result of division of which the Eastern-Slavs people appeared allegedly. According to M. Yu. Braichevskyi, the historical heritage of Kievan Rus is a key problem in the history of Eastern Europe. From the viewpoint of modern European ethnology, the inhabitants of the Southern Rus in X—XIII centuries that were governed by the principalities of Kyiv, Pereiaslavl, Halych had an ancient-Ukrainian ethnic-linguistic specificity, that is, they were Ukrainians at the medieval stage of development. Kievan Rus could not be the first stage of Russian statehood, since it arose long before the birth of the Russians themselves, the scientist believed. Kievan Rus was a product of the efforts of Old Ukrainians at the medieval stage of their development. Analytical thinking, encyclopedic erudition, patriotic adherence elevated M. Yu. Braichevskyi above the Ukrainian historians and archaeologists of 1960-80-ies.